2019
DOI: 10.1037/stl0000147
|View full text |Cite
|
Sign up to set email alerts
|

Think, pair, freeze: The association between social anxiety and student discomfort in the active learning environment.

Abstract: Active learning instructional techniques, often characterized by paired or small group work (e.g., problem solving, discussion), are typically associated with improved student performance.Socially anxious students may, however, experience unique interpersonal and learning challenges due to the social nature of these techniques. Despite its prevalence among college students, little research has examined how social anxiety relates to students experience of active learning, and whether socially anxious students d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…To the extent that a student's expectation of the educational value of a classroom activity predicts how much one is willing to engage in that activity, our data may suggest that first-generation students are at a greater risk of disengaging from active learning classrooms that incorporate practices that they perceive as particularly anxiogenic. Coupled with previous evidence that first-generation students report higher levels of stress during their studies (36), potential risks of using particular active learning practices could be an exacerbation of stress levels and a reduction in these students' commitment to their studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…To the extent that a student's expectation of the educational value of a classroom activity predicts how much one is willing to engage in that activity, our data may suggest that first-generation students are at a greater risk of disengaging from active learning classrooms that incorporate practices that they perceive as particularly anxiogenic. Coupled with previous evidence that first-generation students report higher levels of stress during their studies (36), potential risks of using particular active learning practices could be an exacerbation of stress levels and a reduction in these students' commitment to their studies.…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with this, anxiety stemming from fear of evaluation (test anxiety) correlates negatively with markers of academic success, including grades and SAT scores (34,35). Furthermore, heightened anxiety is associated with greater discomfort in the classroom (36) and greater likelihood of dropping out of a STEM program (37).…”
Section: Introductionmentioning
confidence: 80%
“…However, recent research has indicated that many active-learning techniques can also increase student anxiety or the perceptions of student anxiety (England et al, 2017;Cooper et al, 2018a;Downing et al, 2020) and that students employ both adaptive and maladaptive strategies to cope with this anxiety (Brigati et al, 2020). Ultimately, students with high anxiety may even learn less in an active-learning classroom (Cohen et al, 2019). Some techniques, such as cold-callingasking a student to share a response with the class without the student volunteering-have been identified as producing particularly high anxiety in students (England et al, 2017;Waugh and Andrews, 2020).…”
Section: Shape Active-learning Strategies To Minimize Anxietymentioning
confidence: 99%
“…, 2020 ). Ultimately, students with high anxiety may even learn less in an active-learning classroom ( Cohen et al. , 2019 ).…”
Section: Building An Empowering Atmosphere In the Classroommentioning
confidence: 99%
“…, 2020 ). Highly anxious students experience more discomfort in the classroom ( Cohen et al. , 2019 ), tend toward having lower grades and Scholastic Aptitude Test scores ( Hembree, 1988 ), and are more likely to drop out of a STEM program ( Cassady and Johnson, 2002 ; England et al.…”
Section: Introductionmentioning
confidence: 99%